A safe radio frequency identification system (RFID) authentication protocol for Internet of Things. Issue 1 (March 2021) - Du, Zhiguo; Wen, Bin; Wu, Zhihui; Su, Ruijia; Liu, Wenzi
Abstract: Internet of Things (IoT) is the evolution of related technologies and applications such as Internet and mobile networks. Agriculture, as the source of food, is one of the key areas for the application of the IoT technology, and it is also the field with the most urgent, difficult and integrated characteristics of the IoT application. Future research into IoT will focus on generic technology, information security, and critical applications. Based on IoT, the existing Radio frequency identification system (RFID) security mechanisms are analyzed, with a focus on cryptographic protocols. Investigate the weaknesses or flaws in these protocols, and then a theoretical model and method to design and analyze RFID protocols within the provable security framework is discussed. A mutual authentication protocol of RFID system using synchronized secret information is put forward.